SEDIAAN INSEKTISIDA CALOPHYLLUM SOULATTRI: AKTIVITAS INSEKTISIDA DAN RESIDU TERHADAP LARVA CROCIDOLOMIA PAVONANA DAN KEAMANAN PADA TANAMAN - ., Edy Syahputra, Djoko Prijono (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
Insecticide Preparation of Calophyllum soulattri: Insecticidal and Residual Activity Against Crocidolomia pavonana and Its Savety on Crops. Bioassays were done using leaf-residual method with Crocidolomia pavonana larvae as test insect. The number of dead larvae was recorded daily and was analyzed using probit method. The results showed that methanol extract, and dichloromethane fraction of C. soulattri bark possessed strong lethal effect against C. pavonana larvae with LC50 of 0.15%, and 0.05%, respectively. Dichloromethane fraction of 21 EC and 21 WP sprayed in suspension consentration of 1% on potted broccoli plant had residual activity around 16%-26,7% with range of half-lives of 5.9-7.7 days. Dichloromethane fraction at concentration of 0.2% and 0.3% formulated as EC did not cause phytotoxic to broccoli, tomato, chilli, soybean, red bean, onion, cucumber, and maize. Concerning with this potency, further studies are needed to identify insecticidal compounds.